1994
DOI: 10.1021/np50108a031
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Antimicrobial Activity of Diterpenes from the Roots of Plectranthus hereroensis

Abstract: Two abietane-type diterpenoids have been isolated from the roots of Plectranthus hereroensis (Labiatae), one being the already known horminone [1] and the other a new substance, 7 alpha,12-dihydroxy-17(15-->16)-abeo-abieta-8,12,16-triene-11 ,14-dione [2], whose structure was established by spectroscopic means. Compounds 1 and 2 showed antimicrobial activity against Staphylococcus aureus, Vibrio cholerae, Candida albicans, and Pseudomonas aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 10 publications
2
45
0
1
Order By: Relevance
“…Many plants have been used because of their antimicrobial traits, which are due to compounds synthesized in the secondary metabolism of the plant, such as phenols, 41 essential oils, 42 terpenoids, 43,44 alkaloids, 24 and flavonoids. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Many plants have been used because of their antimicrobial traits, which are due to compounds synthesized in the secondary metabolism of the plant, such as phenols, 41 essential oils, 42 terpenoids, 43,44 alkaloids, 24 and flavonoids. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, da Silva et al (2008) have reported significant MIC values against many grampositive and gram-negative bacteria. Novel antibacterial actions of plant extracts or phytocompounds have been demonstrated, which include inhibition of the MDR-efflux pump (Dixon et al, 1983), -lactamase activity (Tsuchiya et al, 1994), anti-antibiotic resistance properties (Batista et al, 1994), and R-plasmid elimination (Borris, 1996). In our study, most ESL-positive strains resistant to several antibiotics were found to be sensitive to the plant extracts.…”
Section: Resultsmentioning
confidence: 58%
“…Uma triagem ("screening") de avaliação da atividade antifúngica de produtos naturais, em seu estado puro ou "in natura"é considerado como o ponto de partida laboratorial para a prospecção de vegetais com perfil de bioatividade potencial, proporcionando conhecimento sobre a segurança no uso dos mesmos (AFOLAYAN; MEYER, 1997, BATISTA et al, 1994.…”
Section: Descrições Resultados Interpretaçõesunclassified